Kajian Fenomena "No-Show Phenomenon" dalam kalangan calon yang telah ditawarkan kemasukan ke USM - Abd Razak, Nordin; Khairani, Ahmad Zamri; Jamil, Hazri; Ahmad, Mohammad Zohir; Azman, Azlinda; Yaakob, Nooraida (Universiti Sains Malaysia, 2014)
Like any other business institution, a higher education institution such as Universiti Sains Malaysia (USM) needs to understand its customer needs and wants in order to remain competitive and survive among higher education providers. This is also important in order to attract and retain the potential candidates to pursue their studies at Universiti Sains ia (USM), Given an APEX status by the Ministry of Higher Education (MOHE) in 2009, USM has a privilege to screen and select potential students to continuing their studies at the undergraduate level. However, the number of candidate who do not accept USM offer is so high that put USM in an uncomfortable situation. As such, a study on student choice criteria have been carried out, but none have addressed these in USM, as these criteria may be unique to USM. This project aims to explore the factors that influence student choice in the selection of USM as the university for continuing their study at the undergraduate level. Semi-structured and focus-groups interviews were carried out with the first and second year undergraduate students who are continuing their studies at USM as well as prospective students who will apply to continuing their study after completing the study either at the matriculation or secondary schools. Results revealed 25 choice criteria for selecting a university considered by the sample of students interviewed. The factors considered by USM students namely cost, reputation, proximity, job prospect, and parents as the five most important factors. Finally, implications and recommendations are presented.